EFFECT OF BENZENE ON BLOOD PARAMETERS OF MALE MICE - Al-Maliki, Sami (University of Thi-Qar Journal of Science, 2008)
Super and ordinary benzene were used to examine the effect of benzeneon blood parameters of male mice .Three stages with five treated groups wereused. The first stage was after the end of injection period. The second stagewas after 45 days from the end of injection period. Third stage was after 90days from the end of injection period. I.P. injection was used. The results ofthis study indicate the decline of all blood parameters with more reduction inthe mice that were experimented directly after the third injection ( first stage) .Such reduction seems to be slight in animals experimented on 45 days afterthe last injection (second stage ) and little or absent in these wereexperimented 90 days after the last injection (third stage ) .